University Research on Blended Learning in Peru: Fields of Knowledge and Methodological Trends - Turpo-Gebera, Osbaldo (2020)
Blended learning, which has become a normalized mode of teaching, entails new links with educational surroundings and subjects, becoming, in itself, a topic of research and knowledge. This study looks at forty-five undergraduate and graduate student thesis abstracts by students who graduated from universities in Peru and which are archived at the Peruvian Registry for Research Papers (RENAT). Results purport to more thesis executed at the graduate level, particularly in the past five years. There is also evidence of shared research interests between public and private universities. Research on the scientific attributes of BL and the focus on knowledge is more prevalent at universities in Lima, the capital, rather than in provincial areas. In addition, certain research areas were prioritized, such as cognitive studies over procedural and attitudinal; the individual versus the collective whole and disciplinary subject versus cross-cutting. The methodology design, the analyzed theses reveal a penchant towards experimental and correlational designs for descriptive studies on a broad variety of study subjects. This was prevalent not only for students but for school administrators and teachers with a predominance of Likert scale – based questionnaires for data collection prepared by the authors themselves with an emphasis on parametric tests for hypothesis testing.